NILAI HEROISME PADA NOVEL LAUT BERCERITA KARYA LEILA S. CHUDORI : THE VALUE OF HEROISM IN THE NOVEL LAUT CERITA BY LEILA S. CHUDORI - Chaerul; Hamsa, Akmal; Asri, Aswati (Journal of Applied Linguistics and Literature, 2025)
This research is entitled The Value of Heroism in The Novel Laut Bercerita by Leila S. Chudori which aims to describe the value of heroism found in the novel. The method used is a type of qualitative research with a qualitative descriptive design. Data collection techniques were carried out using reading and note-taking techniques. Apart from that, the analysis stage is data reduction, data presentation, and drawing conclusions. The research instrument is a human instrument with checking the validity of the data using theoretical triangulation. The result of the research show that there are five values of heroisme found namely willingness to sacrifice, unity, mutual respect, and enthusiasm and never giving up. In conclusion, this novel has positive values that are useful as learning media or just reading.